Communs culturels et environnement numérique : origines, fondements et identification - Maud PÉLISSIER (Tic & Société)
The privatization of culture over the last several decades gave rise to an intellectual movement which aims to offer an alternative approach to intellectual property by actualizing the old notion of the Commons and its related modes of governance. The aim of this article is to offer an overview of the notion of cultural commons, focusing on its origins, its foundations and its identification.